Antinociceptive activity of Schinus terebinthifolia leaf lectin (SteLL) in sarcoma 180-bearing mice. (15th September 2020) - Ramos, Dalila de Brito Marques; Araújo, Maria Taís de Moura Fontes; Araújo, Tarcísio Cícero de Lima; Silva, Yasmym Araújo; dos Santos, Angela Carolina Lima Amorim; e Silva, Mariana Gama; Paiva, Patrícia Maria Guedes; Mendes, Rosemairy Luciane; Napoleão, Thiago Henrique
Abstract: Ethnopharmacology relevance: Schinus terebinthifolia Raddi leaves have been used in folk medicine due to several properties, including antitumor and analgesic effects. The variable efficacy and adverse effects of analgesic drugs have motivated the search for novel antinociceptive agents. It has been reported that the S. terebinthifolia leaf lectin (SteLL) has antitumor activity against sarcoma 180 in mice. Aim of the study: This work aimed to evaluate whether SteLL would reduce cancer pain using an orthotopic tumor model. Materials and methods: A sarcoma 180 cell suspension was inoculated into the right hind paws of mice, and the treatments (150 mM NaCl, negative control; 10 mg/kg morphine, positive control; or SteLL at 1 and 2 mg/kg) were administered intraperitoneally 24 h after cell inoculation up to 14 days. Spontaneous nociception, mechanical hyperalgesia, and hot-plate tests were performed. Further, the volume and weight of the tumor-bearing paws were measured. Results: SteLL (2 mg/kg) improved limb use during ambulation. The lectin (1 and 2 mg/kg) also inhibited mechanical hyperalgesia and increased the latency time during the hot-plate test. Naloxone was found to reverse this effect, indicating the involvement of opioid receptors. The tumor-bearing paws of mice treated with SteLL exhibited lower volume and weight. Conclusion: SteLL reduced hyperalgesia due to sarcoma 180 in the paws of mice, and this effect can be related to its antitumor action. Graphical abstract: Image 1 Highlights: The lectin SteLL was evaluated for antinociceptive activity on orthotopic tumor model. In the spontaneous nociception assay, SteLL improved limb use during ambulation. The lectin also inhibited mechanical hyperalgesia. SteLL increased the latency time during the hot-plate test. SteLL reduced hyperalgesia due to sarcoma 180 in the paws of mice.